Roux-En-Y Hepaticojejunostomy: An Evaluation Of Its Indications and Results in Benign and Malignant Biliary Tree Disease - Tamang, Tseten Yonjen; Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Journal of Kathmandu Medical College, 2015)
Background: Roux-en-Y Hepaticojejunostomy (RYHJ) is the most common form of reconstruction of the biliary pathway. It is a time honoured, durable, less resource intensive and a definitive procedure. Objectives: The aim of this study was to evaluate the indications of Hepaticojejunostomy and to assess the outcome of surgery following change in surgical technique of Hepaticojejunostomy. Methods: All patients who underwent RYHJ from Magh 2067 (January 2011) till Ashad 2071 (July 2014) in a single surgical unit at the Department of Surgery, Kathmandu Medical College Teaching Hospital were included. Demographics of the patient, indications for surgery, type of surgery, hospital stay and duration of drain placement were evaluated. Since, this is a prospective descriptive study, only mean value was calculated for age, hospital stay and duration of drain placement using SPSS Statistics 17.0 for statistical analysis. Results: Twenty patients underwent RYHJ during the study period. Fifteen percent (n=3) were done for malignant diseases. The most common indication was choledocholithiasis (n=8, 40%) followed by choledochal cyst (n=3, 15%) and bile duct injury (n=3, 15%). The morbidity was minimal. The mean duration of drain in situ was four days (range one to 14 days) and the mean hospital stay was six days (range two to 15 days). Prolonged drain placement and hospital stay was noted in two patients with malignant diseases. However, they were non bilious in nature. We encountered no mortality. Conclusion: Roux-en-Y Hepaticojejunostomy (RYHJ) is a common and safe method of biliary reconstruction. The indication of the procedure is varied and wide. DOI: http://dx.doi.org/10.3126/jkmc.v3i3.12247 Journal of Kathmandu Medical College Vol. 3, No. 3, Issue 9, Jul.-Sep., 2014, page